2021
DOI: 10.3390/antiox10111696
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Rutin and Rutin Glycoside: Antioxidant Activity, Anti-Inflammatory Effect, Effect on Platelet Aggregation and Blood Coagulation

Abstract: The effects of rutin and rutin glycoside with different solubility were compared on antioxidant activity and anti-inflammatory effects in vitro and the effects on platelet aggregation and blood coagulation in vitro and in vivo. Rutin glycoside (consisting of rutin mono-glucoside and rutin di-glucoside) was prepared via enzymatic transglycosylation from rutin. Rutin glycoside showed a higher effect than rutin on radical scavenging activity in antioxidant assays. Rutin showed a higher toxicity than rutin glycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 49 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…Our study showed that the incidence of postoperative lower limb swelling and deep vein in the study group was lower than that in the control group ( P < 0.05). IL-6 and TNF- α are important inflammatory factors that mediate the process of platelet aggregation [ 17 ]. Some scholars believe that inflammatory factors may play key roles in the occurrence and development of LEDVT [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the incidence of postoperative lower limb swelling and deep vein in the study group was lower than that in the control group ( P < 0.05). IL-6 and TNF- α are important inflammatory factors that mediate the process of platelet aggregation [ 17 ]. Some scholars believe that inflammatory factors may play key roles in the occurrence and development of LEDVT [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, RUT showed a slight toxicity against HepaRG cells at the highest concentrations used (50 and 100 µM), whereas the H9c2(2-1) and HaCaT cells were not affected (Figure 3), what indicates a cell-type and concentration-dependent cytotoxic effect. These data are supported by other studies, as follows: 1) no significant impact was induced by RUT in H9c2(2-1) cells (up to 100 μM, after 24 h of treatment) or hepatocytes (up to 500 μg/ ml, after 24 and 48 h of treatment) (Jeong et al, 2009;El-Maadawy et al, 2021); 2) a low cytotoxicity was described in RAW 264.7 macrophages and Vero kidney epithelial cells after 24 h treatment (Mecenas et al, 2018); 3) a significant reduction of RAW 264.7 cells' viability starting with 100 µM (Choi et al, 2021); 4) an inhibitory effect on HaCaT cells' growth (IC 50 = 60 μg/ml) (Deepika et al, 2019); 5) a significant decrease in cell viability of Vero normal kidney cells at 100 and 250 µM after a 48 h treatment (Caparica et al, 2020), and 6) a reduced cell viability of human dermal fibroblasts (HDFs) starting with 50 µM after 24 h exposure (Choi et al, 2016). Moreover, in our previous study concentrations of RUT as high as 75 µM induced a proliferative effect in HaCaT cells (Pinzaru et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Enzymatic hydrolysis and transglycosylation were performed based on the methods described in Baik et al [ 23 ] and Choi et al [ 24 ] with some modification. For the preparation of hesperetin, hesperidin powder was dissolved in 0.1 N NaOH solution at a concentration of 1% ( w / v ).…”
Section: Methodsmentioning
confidence: 99%